Real time monitoring of Aeromonas salmonicida evolution in response to successive antibiotic therapies in a commercial fish farm. (22nd February 2019) - Du, Xiaochen; Bayliss, Sion C.; Feil, Edward J.; Liu, Ying; Wang, Chao; Zhang, Gang; Zhou, Dongsheng; Wei, Dawei; Tang, Na; Leclercq, Sébastien O.; Feng, Jie
Summary: Our ability to predict evolutionary trajectories of pathogens in response to antibiotic pressure is one of the promising leverage to fight against the present antibiotic resistance worldwide crisis. Yet, few studies tackled this question in situ at the outbreak level, due to the difficulty to link a given pathogenic clone evolution with its precise antibiotic exposure over time. In this study, we monitored the real‐time evolution of an Aeromonas salmonicida clone in response to successive antibiotic and vaccine therapies in a commercial fish farm. The clone was responsible for a four‐year outbreak of furunculosis within a Recirculating Aquaculture System Salmo salar farm in China, and we reconstructed the precise tempo of mobile genetic elements (MGEs) acquisition events during this period. The resistance profile provided by the acquired MGEs closely mirrored the antibiotics used to treat the outbreak, and we evidenced that two subclonal groups developed similar resistances although unrelated MGE acquisitions. Finally, we also demonstrated the efficiency of vaccination in outbreak management and its positive effect on antibiotic resistance prevalence. Our study provides unprecedented knowledge critical to understand evolutionary trajectories of resistant pathogens outside the laboratory.